ANALISIS KUALITAS LAYANAN PERBANKAN DENGAN KONSEP SERVQUAL - Eka Dyah Setyaningsih (Universitas Bina Sarana Informatika, 2014)
The banking sector is an important sector in the economy which will run inside transactions. This factor is the quality of service that should always be improved to attract customers in the deal in order to feel comfortable and continue to use the banking services. Object of research that the authors take is the quality of service that consists of physical evidence, reliability, responsiveness, assurance, empathy. The quality of service to the concept of servqual can see the difference between perceptions and expectations of customers are according to customer expectations. If the expectation is smaller than the perception of these should be repaired again, and if the expectation is already larger than the perception of these should be maintained in a manner that is effective and efficient. Based on these results it can be stated that not all met the expectations of customers still have no sustainable improvements to the quality factors of the service. Keywords : Banking, Concept Servqual, Quality of Service